2022
DOI: 10.1039/d2ra00788f
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic hydrogen evolution over cyanine-sensitized Ag/TiO2

Abstract: Comparison between photo- and sonophotocatalytic hydrogen production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Since hydrogen production from water splitting is an uphill reaction, studies have shown that adding a small amount of commercial reagents during the reaction can significantly improve the photocatalytic effect. Almazroai et al 27 found that adding 200 mL of methanol can increase the photocatalytic reaction rate by a factor of 9. In this work, 10 wt % triethanolamine was added as a hole scavenger during the photocatalytic process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Since hydrogen production from water splitting is an uphill reaction, studies have shown that adding a small amount of commercial reagents during the reaction can significantly improve the photocatalytic effect. Almazroai et al 27 found that adding 200 mL of methanol can increase the photocatalytic reaction rate by a factor of 9. In this work, 10 wt % triethanolamine was added as a hole scavenger during the photocatalytic process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After entering the photocatalytic era, photocatalytic water decomposition to produce hydrogen has become one of the most promising ways of solar energy conversion and storage to solve these problems. H 2 production by photolysis of water has made great progress in recent decades, and various semiconductor materials (including oxides, carbides, sulfides, nitrides, and phosphides) have been developed into available photocatalysts. Up to now, the photocatalysts that have been widely studied include TiO 2 , g-C 3 N 4 , WO 3 , CdIn 2 S 4 , ZnIn 2 S 4 , BiVO 4 , , etc., all of which have excellent photocatalytic performance. However, the photocatalytic performance and stability of many photocatalysts still need to be improved, so it is of great practical significance to study photocatalytic technology and develop efficient photocatalysts …”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these challenges, doping with metal/nonmetal elements, or compositing TiO 2 with metal, nonmetal, and other semiconductors are effective ways to improve the photocatalytic activity. Constructing heterojunctions is regarded as an effective way to improve the utilization efficiency of solar light and suppress the recombination of electrons/hole pairs by building an internal electric field at the heterojunction interface. The perovskite-typed materials (ABO 3 ) have become much more popular due to their superior photocatalytic activity under both UV and visible light irradiation. Their structure is very stable and flexible by varying the composition of A and B sites to optimize the electronic and catalytic properties. Among them, zinc titanate (ZnTiO 3 ) is one of the most promising photocatalysts to be applied in the degradation of pollutants and water splitting, which is considered as an ideal candidate to couple with TiO 2 for improving the photocatalytic performance of TiO 2 via creation of heterojunctions.…”
Section: Introductionmentioning
confidence: 99%
“… 16 19 Constructing heterojunctions is regarded as an effective way to improve the utilization efficiency of solar light and suppress the recombination of electrons/hole pairs by building an internal electric field at the heterojunction interface. 20 22 The perovskite-typed materials (ABO 3 ) have become much more popular due to their superior photocatalytic activity under both UV and visible light irradiation. 23 25 Their structure is very stable and flexible by varying the composition of A and B sites to optimize the electronic and catalytic properties.…”
Section: Introductionmentioning
confidence: 99%